Analysis of Critical Thinking Ability in Trisakti University Students’ Learning Writing Argumentation - Haryanti, Ade Siti; Hidayat, Sholeh; Juansah, Dase Erwin (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study aims to determine critical thinking skills in learning to write arguments in semester 2 students of the Faculty of Law, Trisakti University in Indonesian Law courses. The sample of this research was 80 students consisting of 2 classes using purposive sampling technique. Data collection techniques are by observation, tests, and interviews. The data analysis technique uses descriptive qualitative analysis. The results showed that: (1) students’ critical thinking skills were 75% above the average, and 25% of the respondents’ answers were below the average. The highest indicator is formulating an appropriate question from an argumentation text of 83.55% and the lowest indicator is analyzing problems from an argumentation text of 63.45%, (2) efforts to develop students’ critical thinking in learning to write arguments through assignments, questions and answers as well as providing direction, (3) the obstacles faced by students in developing critical thinking in learning to write are students’ difficulties in solving problems and difficulties in expressing ideas and ideas into written form. While the obstacles faced by lecturers are that lecturers have never made a special assessment regarding critical thinking, this is because lecturers do not understand the indicators of critical thinking and do not understand the appropriate methods and techniques in developing critical thinking skills in learning to write arguments.